Determinasi Kinerja Keuangan Perusahaan Manufaktur: Peran Modal Intelektual, Struktur Modal dan Ukuran Perusahaan - Rr Yoppy Palupi Purbaningsih (BADAN PENERBIT STIEPARI PRESS, 2026)
Knowledge plays a crucial role in corporate value, as this asset significantly determines the company's overall value. These intangible assets include positive shareholder equity, strong financial performance, the company's intellectual capabilities, and cost efficiency, which can drive improved financial performance and competitive advantage. All of these factors contribute to continuous innovation, known as intellectual capital. Company size, as reflected in its assets, indicates the company's level of prosperity. Additional financing in the form of capital is used wisely to support company operations, thereby increasing profits. The subjects of this study were companies operating in the manufacturing sector and listed on the Indonesia Stock Exchange (IDX). The observation period ran from 2020 to 2024. The complete sample in this study consisted of 16 companies selected using a purposive sampling technique. Sample data were collected using a purposive sampling method, while data analysis was conducted using eViews. The results revealed that, separately, Intellectual Capital had a significant impact on Financial Performance. Conversely, Capital Structure and Company Size did not show a significant influence on Financial Performance when viewed separately. However, simultaneously, Intellectual Capital, Capital Structure, and Company Size have a significant influence on Financial Performance.